Differential tolerance of bean genotypes to the herbicides fomesafen, imazamox and S-metolachlor - Carlos Zacarias Joaquim Júnior; Paulo Henrique Cerutti; Luan Tiago dos Santos Carbonari; Inácio João Barbosa; Marcio dos Santos; Jefferson Luís Meirelles Coimbra; Antonio Mendes de Oliveira Neto; Altamir Frederico Guidolin (Ciência Rural)
ABSTRACT: Beans are one of the most important legumes for humans, requiring the adoption of strategies that can improve their productivity, such as the use of herbicides. The study identified bean genotypes tolerant to fomesafen, imazamox and S-metolachlor belonging to different herbicides mechanisms of action, for use in the improvement of new tolerant cultivars and to verify the influence of their morphogenetic aspects on the response to herbicides. The trial was carried out in randomized blocks, in a 4x15 factorial design, with four replications. The first factor consisted of the herbicides fomesafen, imazamox, S-metolachlor and control (without herbicide). The second factor was composed of the genotypes Caviano, IPR Uirapurú, IPR Tuiuiú, IPR Campos Gerais, BRS Pérola, BRS Campeiro, BRS Estilo, BAF03, BAF07, BAF36, BAF51, BAF235, BAF238, BAF239 and BAF240. Phytotoxicity, chlorophyll, number of leaves, stem diameter, plant height, dry mass of the aerial part, number of pods per plant, number of grains per pod and grain production per plant were evaluated. Data were subjected to backward elimination analysis, MANOVA and multivariate contrasts. It was observed that the accessions (BAFs) were less tolerant than cultivars. Cultivars such as BAF238, BAF239, BAF51, BAF36 and BAF03 were identified as the most sensitive to herbicides, while the cultivars BRS Pérola, IPR Campos Gerais, Caviano and BAF07 were the most tolerant, taking into account the different modes of action of herbicides.